TEOLOGI MISI TRANSFORMATIF DAN INKLUSIF DALAM PERJANJIAN BARU SEBAGAI BASIS PENGABDIAN KRISTIANI KEPADA MASYARAKAT - Marde Christian Stenly Mawikere; Sudiria Hura (PT. Giat Konseling Nusantara, 2025)
Mission theology in the New Testament presents a transformative and inclusive understanding, which is not merely confined to the dissemination of faith teachings, but also as an active participation in the work of God's salvation revealed through Jesus Christ. The mission of Christ brings salvation that embraces all people, irrespective of ethnicity, gender, or social status. Through the early church, this mission developed into a universal calling leading to liberation and social reconciliation. This study aims to uncover the transformative and inclusive dimensions in New Testament mission theology, as well as its relevance for Christian service to contemporary society. The findings indicate that Christian mission should encompass social empowerment, justice, and tangible acts of love in service to the community, as a concrete testimony to the Kingdom of God.